Institucionalidad, eficacia y desafíos de la democracia - Ricardo Uvalle Berrones (Revista del CLAD Reforma y Democracia, 2007)
democracy: Citizenship This document analyzes the dynamics of the contemporary democracy with base in its values, processes and rules that nourish their institutional character to articulate the plural and differentiated coexistence. It has the society, the State, the market and the citizens as central points. It also considers the importance of competition, costs of democracy, interchanges, incentives and restrictions that structure a way of coexistence. The government of democracy requires capacities oriented to obtain that the individual and collective sphere has an effective performance in the scope of increasing exigencies that demand Institutions, Efficacy and Challenges of Democracy Ricardo Uvalle Berrones pragmatism to assure stability and governance. This compromises the governors with the governed ones in the logic of the commitments, the expectations, the projects of life, and the fulfillment of goals to fortify the legitimacy of the public power, with constructive actions that avoid the extension of the social evils. It is necessary to assure the efficient yields of the market economy and the consolidated use of the Rule of Law for avoiding the existence of economic, political, administrative, public and legal costs that could diminish the productive and social activities